A research capacity strengthening project for infectious diseases in Honduras: experience and lessons learned - Ana Lourdes Sanchez; Maritza Canales; Lourdes Enriquez; Maria Elena Bottazzi; Ada Argentina Zelaya; Vilma Esther Espinoza; Gustavo Adolfo Fontecha (Taylor & Francis Group, 2013)
Background: In Honduras, research capacity strengthening (RCS) has not received sufficient attention, but an increase in research competencies would enable local scientists to advance knowledge and contribute to national priorities, including the Millennium Development Goals (MDGs). Objective: This project aimed at strengthening research capacity in infectious diseases in Honduras, focusing on the School of Microbiology of the National Autonomous University of Honduras (UNAH). The primary objective was the creation of a research-based graduate program for the continued training of researchers. Parallel objectives included institutional strengthening and the facilitation of partnerships and networks. Methods: Based on a multi-stakeholder consultation, an RCS workplan was designed and undertaken from 2007 to 2012. Due to unexpected adverse circumstances, the first 2 years were heavily dedicated to implementing the project's flagship, an MSc program in infectious and zoonotic diseases (MEIZ). In addition, infrastructure improvements and demand-driven continuing education opportunities were facilitated; biosafety and research ethics knowledge and practices were enhanced, and networks fostering collaborative work were created or expanded. Results: The project coincided with the peak of UNAH's radical administrative reform and an unprecedented constitutional crisis. Challenges notwithstanding, in September 2009, MEIZ admitted the first cohort of students, all of whom undertook MDG-related projects graduating successfully by 2012. Importantly, MEIZ has been helpful in expanding the School of Microbiology's traditional etiology-based, disciplinary model to infectious disease teaching and research. By fulfilling its objectives, the project contributed to a stronger research culture upholding safety and ethical values at the university. Conclusions: The resources and strategic vision afforded by the project enhanced UNAH's overall research capacity and its potential contribution to the MDGs. Furthermore, increased research activity and the ensuing improvement in performance indicators at the prime Honduran research institution invoke the need for a national research system in Honduras.